UMP launched MyGift programme as a channel for university endowment contribution - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) launched MyGift Programme in a bid to raise fund from the public and private bodies to be utilised for education sponsorship, setting up infrastructure and facilities for undergraduates as well as to nurture the culture and spirit of giving to the needy.